The Interplay of Sufi Movements, Arts, and Cultural Expression in the Contemporary Era - Syahuri Arsyi (SUHU: Journal of Sufism and Humanities, 2026)
Objective: This study examines the relationship between Sufi movements and the arts in the contemporary era. While previous scholarship has primarily explored Sufism as a spiritual and theological tradition, comparatively little attention has been given to the role of the arts as a medium of cultural expression, religious communication, and social transformation within contemporary Sufi movements. Method: This study employs a library research design using a descriptive-historical approach. Data were collected through a systematic review and critical analysis of scholarly literature on Sufism, the arts, culture, and contemporary Sufi movements to identify recurring themes and conceptual patterns. Results: The findings reveal that the relationship between Sufi movements and the arts operates through two complementary dimensions. The first is the esoteric dimension, in which the arts function as an integral component of spiritual practice and a means of inner refinement for Sufi practitioners, particularly within the ṭarīqa tradition. The second is the exoteric dimension, in which the arts serve as a medium for communicating Sufi teachings and transmitting spiritual values to wider audiences through culturally embedded, aesthetically engaging, and socially inclusive forms of expression. Conclusion: This study concludes that the arts should be understood not merely as vehicles of aesthetic expression but also as strategic instruments for communicating and transmitting Sufi teachings in contemporary society. By conceptualizing the esoteric and exoteric dimensions of Sufi art, this research contributes to the development of Islamic Sufism studies by offering a more comprehensive framework for understanding how Sufi movements negotiate spirituality, culture, and social transformation in the modern era.